Implications of variation in resin composition among organs, tissues and populations in the tropical legume Hymenaea. - Langenheim, J. H.; Stubblebine, W. H.; Lincoln, D. E.; Foster, C. E.
Variation in leaf blade, petiole and primary stem resins, composed of sesquiterpene hydrocarbons, is analysed in two contrasting species of the tropical legume Hymenaea. Five populations of the New World H. courbaril, spanning a wide range of ecosystems, are compared with a population of the disjunct African H. verrucosa. Resins in petiole and primary stem tissue are similar, but differ significantly in total composition from leaf blade tissues. The major components, caryophyllene, ?- and ?-selinene and ?-copaene vary most significantly among the tissues, but all compounds vary at highly significant levels among populations. The variation patterns in resin composition among the leaf blade and petiole/primary stem tissues are put into a larger context of comparison with the primarily diterpenoid patterns in secondary stem and pod tissues. Although the comparatively minor quantitative differences in the sesquiterpene systems could be attributed solely to developmental and physiological differences among the tissues and populations, the total weight of accumulating evidence regarding quantitative variation and demonstrated toxic and deterrent properties of sesquiterpene resins to insect herbivores leads us to hypothesize a possible role of differential predator pressures.
Keywords: HYMENAEA; LEGUMINOSAE; SESQUITERPENES; DITERPENOIDS; TISSUE AND ORGAN VARIATION; POPULATION VARIATION; HERBIVORE SELECTIVE PRESSURES